Relevansi Nilai Informasi Modal Intelektual Studi Empiris Pada Perusahaan Perbankan Di Bursa Efek Indonesia - Sutoyo Sutoyo (Jurnal Paradigma, 2014)
The purpose of this study was to test the value relevance of accounting information book value per share and earnings per share information and intellectual capital . Intellectual capital is measured using value added intellectual coef cient models ( VAIC TM ) used by Ante Pulic. This study was performed using Ohlson models and VAIC TM as additional information in the model to test the value relevance of intellectual capital accounting information , as other information on the company’s stock price . Companies listed in the Stock Exchange ‘s banking industry classi cation in 2010 was as much as 30 company , in 2011 as many as 31 companies and in 2012 as many as 32 companies . Based on the criteria used in this study , the company was selected as a sample of 30 companies for 3 years . The results showed that the ef ciency of the components of intellectual capital in the form of physical and nancial capital has relevance value . The ef ciency of the components of intellectual capital in the form of human capital has a relevance value . The ef ciency of the components of intellectual capital in the form of structural capital has a relevance value